PEMANFAATAN LIMBAH TONGKOL JAGUNG (ZEA MAYS) UNTUK PRODUKSI BIOETANOL MENGGUNAKAN SEL RAGI AMOBIL SECARA BERULANG - Indriany, Dewi; Mappiratu, Mappiratu; Nurhaeni, Nurhaeni (Natural Science: Journal of Science and Technology, 2013)
Study about the Utilization of corn cob waste (Zea mays) for Bioethanol production using immobilized yeast cells repeated used has been done. The aim of this research was to find both the ratio of sulfuric acid to corn cob wheat and the hydrolysis time in order to get the high sugars content, and to know the activity of the immobilized yeast cell for alkohol content during repeated use. It was done by apply  5 levels of surfuric acid (50%) ratio to corn cob wheat and 5 levels of hydrolysis. It was 1 : 1 (A), 2 : 1 (B), 3 : 1 (C), 4 : 1 (D), and 5 : 1 (E) based on v/b and 0,5; 1;  1,5;  2; and 2,5 hours respectively. The result showed that the best ratio of sulfuric acid to corn cob wheat was 5 : 1 (v/b), it produced the sugars content for about 41,63%. While the best hydrolysis time was 1,5 hours and it gaved 43,75% of sugars content. The sugar Fermentation was done in 48 hours. The activity of immobilized yeast cell using sulfuric acid hydrolysis product getting decreased in repeated used, and there was no alcohol producted at the fourth time of immobilized yeast cell used.